¿Es la práctica odontológica un trabajo social descontextualizado? - Carlos Payares-Gonzalez (Universidad de Antioquia, 1996)
Because of the discrimination suffered for the dentistry during the last century and enough time of the present century, this practice developed her knowledges like a "black box", whose technological foundation was undecipherable for the secular and another sanitary prctices. Around that time, the discrimination reverted in a monopoly, and the monopolyin a operative autonomy that facilitated the professionalism process. However, this circumstance, that was positive historically in order to a professionalism process, was negative in order to the scientific and academic foundations of the dentistry.